Child, Parental, and Household Factors on Inactivated Poliovirus Vaccine Use - Tutut Okta Hardiyanti; Ayun Sriatmi; Martini; Sutopo Patria Jati; Budiyono; Novia Handayani; Aditya Kusumawati (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2026)
Although the immunization program requires OPV vaccine for every infant, outbreaks of polio and Acute Flaccid Paralysis (AFP) still occur frequently, triggering a rapid response of mass immunization. The vaccine of Inactivated Polio Virus (IPV) was added to prevent wild poliovirus which causes paralysis, but its effectiveness has not been optimal. The study purpose was to analyse the effect of child characteristics, perceptions, parental hygiene practices, and house's physical conditions on the IPV vaccination utilization. This study was quantitative survey with a cross-sectional approach. The population was all children aged <7 years in Central Java Province. A sample of 1,069 children was obtained through convenience sampling from 15 districts/cities serving as RCA locus for 2024 Polio SubPIN activities. Data collection was conducted through observations using the KIA Handbook, home visits, and interviews using a questionnaire. Data was analysed using descriptive, bivariate, and multivariate. The results showed that 85.9% of children utilized 4-doses OPV vaccination completely and 83.6% utilized the first dose of IPV vaccination. It was proven that OPV immunization status, parental hygiene practices, and house's physical condition were associated with IPV vaccine utilization, both partially and simultaneously. The effect of three variables was 27%, with OPV immunization status being the main predictor. There was a 3.54-fold increase in IPV utilization if OPV status was complete, followed by parental hygiene (OR=2.02) and the house's physical condition (OR=1.56). More intensive socialization regarding IPV vaccination is needed through personal communication interventions that can also motivate parents. Strengthening the vaccination service system by providing vaccine stocks and cold chains as needed, regulatory support, and effective IEC are key factors in the success of IPV vaccination